Frontiers and Progress in Multiphase Flow I - Cheng, Lixin.; Cheng, Lixin. (Frontiers and Progress in Multiphase Flow,, 2014)
This volume presents state-of-the-art of reviews in the field of multiphase flow. In focusses on nonlinear aspects of multiphase flow networks as well as visualization experiments. The first chapter presents nonlinear aspects or deterministic chaos issues in the systems of multi-phase reactors.  The second chapter reviews two-phase flow dynamics in combination with complex network theory. The third chapter discusses evaporation mechanism in the wick of copper heat pipes. The last chapter investigates numerically the flow dynamics and heat and mass transfer in the laminar and turbulent boundary layer on the flat vertical plate.